Role of self-awareness in the promotion of health and well-being of college students - Rekha Wagani; Pranita Gaur (Archives of Depression and Anxiety - Peertechz Publications, 2024)
The quest for knowing self is the most basic of human nature, which is long believed to be necessary for promoting good health and well-being. This research provides a theoretical and empirical examination of the role of Self-Awareness (SA) in health and well-being. It was proposed that self-awareness is a positivistic construct that would promote health and well-being. In order to achieve the above-stated purpose, two series of studies were planned. The first study aimed to find out the contribution of SA to various dimensions of health and well-being. A total of 300 college students equally drawn from both genders participated in the study. The self-awareness scale (developed by the researcher), health scale for college students (adapted for the present study), and WHO spirituality form were given to participants. Study I demonstrated that self-awareness predicted most health and well-being factors. The findings further suggested that self-awareness may promote health and well-being. In study II, 60 experimental-control group participants were recruited. Students were allocated into experimental and control groups. A specifically designed Self-awareness Intervention Program (SAIP) was held for five days for the participants in a controlled setting. The results showed a substantial increment in the health and well-being of the treatment group in comparison to the control group. A brief follow-up interview was conducted to understand the Intervention's results. A major implication of the present study is that SA can be used as a positivistic construct and that an intervention program can be taken as a low-cost strategy to promote the health and well-being of college students.